Two Models of Ownership: How Commons Has Co‐Existed with Private Property. (March 2016) - Tabachnick, David
Abstract: This article challenges the claim by many historians that the rise of capitalism requires the destruction of common property systems. In contrast to the English case in which commons were enclosed, French peasants used their common property system to regulate the market, provide a rural safety net and a democratic check on elites, while urban industry developed. European battles over common property replayed in surprising ways in colonial African countries such as Sierra Leone, and echoes reemerge today. The West African country of Guinea tests two possible paths to development of a market society: the English path and the French path. Interviews with key government officials collected in 1993 help explain why Guinea, despite adopting a land law in 1992 inspired by the English path, has so far failed to widely apply the law and, in fact, is following the French path. The United States pursued a policy of replacing American Indian common property systems with exclusive individual property rights. Nonetheless, Indian common property survives in the form of recent recognition of Indian off‐reservation hunting and fishing rights. The Menominee reservation successfully resisted the destruction of its common property system and today participates in the market in a manner that preserves reservation ecology, democratic government, and Menominee cultural identity. Rethinking the meaning of French, African, and U.S. accommodation to common property systems offers important lessons for contemporary development policies in Africa and around the world.